Evaluation of Abattoir Practices in Ijebu Ode, Nigeria - OTTO, Edet (International Journal of Advances in Life Science and Technology, 2022)
If used properly, abattoirs can help with disease management, ante- or postmortem investigation of animals and the meat, and can protect the population from most zoonotic illnesses that can develop after eating unsanitary, unsafe, or unwholesome meat or meat products. This underscores the need to examine and explore present abattoir practises in order to better understand the current situation of meat production in Ijebu Ode, Nigeria. Data was retrieved from three (3) government-approved abattoirs using self-administered structured questionnaires, personal interviews, and observations, and the data were computed descriptively using a statistical software for social scientists. Findings from the empirical observation and evidence indicated significant deficiencies in the essential hygiene facilities and services, with the lack of a veterinary laboratory for microbiological confirmation of suspected meat, and all the butchers reported no utilisation of protective gear during slaughtering activities. 66.7% of the abattoirs disposed of their solid waste by open dumping in the nearby bushes, while the wastewater was discharged into public drains. The study revealed that the abattoir practises in Ijebu Ode are unsatisfactory, with unsanitary practises and shortfalls in fundamental hygiene facilities and services, which are critical for producing healthy meat for public consumption. As a result, standardisation of facilities, including the closure of substandard ones, and educational training of abattoir workers were proposed as ways to improve hygiene facilities and practises.